Economic Valuation of Bifemnasi Sonmahole Forest Area (Case: Taekas and Femnasi Village in North Central Timor Regency) - Werenfridus Taena; Yeremias Binsasi; Willem Amu Blegur; Remigius Binsasi (Jurnal Ilmu Lingkungan, 2025)
The Bifemnasi-Sonmahole Forest Area is a forest area covering three districts on the border of Indonesia and Timor Leste. This forest area provides benefits, especially in Taekas and Femnasi Villages, TTU Regency, where water sources from this forest area supplied the water needs of Kefamenanu City from 1970 to 2000, but currently only fulfill the needs of the residents of Taekas and Femnasi Villages. This research aims to analyze the economic valuation of the Bifemnasi-Sonmahole forest area in Taekas and Femnasi Villages, North Central Timor Regency. The research used a survey method. Data was obtained by observation, interviews, and documents study. The sample was determined in stages, namely cluster and purposive sampling, with a total sample of 60 people to represent direct use value, indirect use value and non-use value. Data analysis used market price method, travel costs, preventive cost, transfer benefits. The results showed that the benefit value of the Bifemnasi-Sonmahole forest area in Taekas and Femnasi Villages, North Central Timor Regency is IDR 3,347,524,400, - obtained from a Direct Use Value of IDR 236,210,000,- (7.06%); Indirect Use Value is IDR 2,296,438,400 (68.60%) and Non Use Value is IDR 814,876,000 (24.34%).